PERANCANGAN PENGUKURAN TEGANGAN TINGGI PADA MODUL PEMBANGKIT TEGANGAN TINGGI IMPULS - Pravitasari, Chyntia Dewi Candra; Syakur, Abdul; Setiyono, Budi (Universitas Diponegoro, 2018)
Measurement of high voltage AC, DC and Impulses on a laboratory scale using expensive measuring instruments. In addition, the measurements taken are at a voltage level of 15 KV. Integrated measurement of high voltage AC, DC and Impulses for 15 KV voltage levels using sign transformers has never been done. Whereas high voltage generation using a sign transformer is only able to generate voltage up to 15 KV voltage only. For that we need a voltage measuring device that is able to measure up to a voltage of 15 KV, and does not require expensive costs. In this Final Project, a high voltage monitoring module for impulse high voltage generator module will be designed using visual studio c #. The results of monitoring the high voltage generator module on the C # visual studio form successfully went well. The voltage test performed produces a value close to the actual value with an average error of 0.01 volts. Unfortunately this test is still not perfect because it is still susceptible to noise so that the measurement process is often interrupted.